PROSEDUR PELAYANAN ADMINISTRASI PEMBAYARAN GAJI PENSIUN PEGAWAI NEGERI SIPIL PADA PT. TASPEN (PERSERO) CABANG MALANG - Arakian .; Willy Tri Hardiyanto; Nanang Bagus (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2015)
Abstract: Public service is a set or a number of activities undertaken by the government or the public bureaucracy required to meet the needs of the community. Good service and customer satisfaction accepted procedures should be followed by application of a good service anyway. Procedure for payment of pension administration civil servants are granting civil rights by the government in the form of salary or severance pay in accordance with applicable laws. In this research, administrative services already implemented systems and procedures based computer/web, so that the service does not require the administration of pension payments for a long time. Standard delivery time is 30 minutes for the Letter Request Payment (SPP) Klim immediately, and 60 minutes for SPP Klim indirect complete all requirements.vIt can be concluded that the procedure for payment of pension administration civil servants really nice to be able to answer the needs of administrative services in accordance with the nature and principles of public service. It is recommended to continue to improve service systems and procedures as well as maintain a good image in customer service. Keywords: Public Service, Service Procedures Abstrak: Pelayanan publik merupakan serangkaian atau sejumlah aktifitas yang dilakukan oleh pemerintah atau birokrasi publik untuk memenuhi kebutuhan yang diperlukan oleh masyarakat. Pelayanan yang baik maupun kepuasan yang diterima pelanggan harus diikuti dengan penerapan prosedur pelayanan yang baik pula. Pada penelitian ini, pelayanan administrasi yang diterapkan sudah melalui sistem dan prosedur yang berbasis komputer/web, sehingga pelayanan administrasi pembayaran pensiun tidak memerlukan waktu yang lama. Waktu pelayanan yang standar yaitu 30 menit untuk Surat Permintaan Pembayaran (SPP) Klim langsung, dan 60 menit untuk SPP Klim tidak langsung sepanj ang persyaratan lengkap.Dapat disimpulkan bahwa prosedur pelayanan administrasi pembayaran pensiun pegawai negeri sipil benar-benar baik sehingga mampu menjawab kebutuhan pelayanan administrasi sesuai dengan hakekat dan prinsip pelayanan publik. Disarankan untuk terus meningkatkan sistem dan prosedur pelayanan yang baik serta menjaga citra baik dalam pelayanan terhadap pelanggan. Kata Kunci: Pelayanan Publik, Prosedur Pelayanan